Attitude Toward AI Use, Extent of AI Tool Utilization, and Administrative Efficiency among School Heads in SAMARICA District - Manayam, Joshua (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationships among elementary school heads’ attitudes toward artificial intelligence (AI), their extent of AI utilization, and their administrative efficiency in the SAMARICA District of Occidental Mindoro. Anchored on the Technology Acceptance Model, Task–Technology Fit theory, and Diffusion of Innovations theory, the research employed a descriptive correlational design to analyze existing conditions and relationships among variables. Data were collected from 98 public elementary school heads identified as AI users through a structured survey instrument with high internal consistency. Descriptive and inferential statistical techniques, including correlation and regression analysis, were used to assess levels of attitudes, utilization, and efficiency, as well as the mediating role of utilization. Findings revealed that school heads demonstrated positive attitudes toward AI, characterized by high levels of interest, trust, and perceived usefulness, alongside moderate fear. The extent of AI utilization was high, particularly in terms of frequency, integration, and confidence, although functional breadth remained moderate. Administrative efficiency was also high, especially in task management and communication, with moderate levels in decision-making and resource utilization. Significant positive relationships were found among attitudes, utilization, and efficiency, with utilization emerging as the strongest predictor. Furthermore, AI utilization fully mediated the relationship between attitudes and administrative efficiency, indicating that positive attitudes enhance performance only when translated into actual and consistent AI use. The study concludes that effective AI integration in school leadership depends on both positive perceptions and practical application, and it recommends expanded training, institutional support, and broader research coverage. The findings support SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by highlighting the role of AI in improving educational leadership and productivity. In terms of sustainability, the study contributes to institutional and technological sustainability by promoting efficient, data-driven school governance and strengthening capacity for digital transformation in resource-constrained educational settings.